Long‐term ungrounded cable support for short‐to‐shield syndrome. Issue 3 (7th February 2020) - Ayers, Brian; Cheyne, Christina; Wood, Katherine; Quinlan, Amy; Dick, Sara; Vidula, Himabindu; Alexis, Jeffrey; Barrus, Bryan; Prasad, Sunil; Gosev, Igor
Abstract: Short‐to‐shield (STS) is a potential complication for left ventricular assist device (LVAD) patients supported by the HeartMate II (HMII) pump. This phenomenon occurs when a damaged internal wire within the driveline makes contact with the surrounding sheath, resulting in insufficient power delivery to the motor when connected to a grounded power base unit (PBU). An ungrounded cable can be used to negate these effects, but the long‐term safety of this treatment strategy is unknown. In this case series, we present our institutional experience treating 17 STS patients with an ungrounded cable. In total, we present 4922 patient‐days (13.4 patient‐years) of ungrounded cable support after primary STS treatment. There were no deaths or complications related to STS. These data suggest that the long‐term use of an ungrounded cable is a reasonable treatment option for patients who cannot or do not wish to undergo pump exchange or splice repair. Abstract : Patients that experience short‐to‐shield can be safely managed with an ungrounded cable long‐term with careful monitoring.